آل فرعون پر آفات سماویہ (آیات تسعہ) کا اسلامی تعلیمات اور بائبل کی روشنی میں تقابلی جائزہ: A Comparative Analysis of the Natural Disasters (Ayat-e-Tis’ah) on the Pharaohs in the Light of the Islamic Teachings and the Bible - Dr. Atiq Ullah,; Dr. Zia Ur Rehman,; Dr. Muhammad Zakariya, (Al Manhal Research Journal, 2023)
When Moses (علیہ السلام) invited Pharaoh and his people to Islam, they did not accept the invitation of Moses (علیہ السلام) and demanded miracles from Moses (علیہ السلام). Moses (علیہ السلام) performed miracles at Pharaoh's demand, but still Pharaoh and his people refused to believe and continued to persecute the Israelites, as a result of which Pharaoh's people faced calamities. These miracles of Musa (علیہ السلام) and these calamities that befell Pharaoh's family have been named in the Qur'an as Ayat-e-Tis’ah. These disasters are mentioned in various interpretations of the Noble Qur’an and in the Bible. Ayat-e-Tis’ah refers to the nine miracles of Moses, out of which seven are coincidental while there is difference in the determination of two miracles. Coincidental miracles refer to the Stick of Musa (علیہ السلام), the Bright Hand, the Storm, the Locusts, the Lice, the Frogs, and the Blood. Now, in the description of these miracles, some things are same in the Islamic teachings and in the Bible while there are differences in some things, which we will discuss in this article.